When typical clinical signs are not enough: overdiagnosis of canine hypothyroidism in Costa Rica - Castro, Esteban (2024)
Canine hypothyroidism is the most common endocrine disease in dogs and is often overdiagnosed. The purpose of this study is to analyze the importance of testing TSH together with free Thyroxine (fT4) to differentiate between true hypothyroid cases and suspected cases with clinical signs suggestive of hypothyroidism and identify if there is any level of canine hypothyroidism overdiagnosis. There were 48 individuals in the control group (clinically healthy animals) (CT), 40 with clinical signs but with no laboratory confirmation (SHT), and 41 with laboratory confirmation (HT). Significant differences were obtained between the HT group and the C and SHT groups in both hormone values, but not between the C and SHT groups. A diagnosis solely based on clinical signs rather than laboratory diagnostic methods, the use of a single hormone test, the method used for measuring hormones, and any possible interference can cause false positives in the diagnosis of canine hypothyroidism. Therefore, all these factors must be considered when making a diagnosis, leading the clinician to use a multiple-approach diagnosis rather than a single-approach diagnosis.